Performance Investigation on the High-Resolution Wide-Swath SAR System with Monostatic Architecture - Bordoni, Federica; Younis, Marwan; Gebert, Nicolas; Krieger, Gerhard; Fischer, Christian (European Conference on Synthetic Aperture Radar (EUSAR), 2010)
The High-Resolution Wide-Swath (HRWS) Synthetic Aperture Radar (SAR) system, promoted by EADS Astrium GmbH, has been object in the last years of intensive studies for his capability to overcome the conflict between azimuth resolution and swath width of conventional SAR. The original choice of a bistatic solution for the system architecture has been recently reconsidered and is currently oriented towards a monostatic approach. The paper reports a performance analysis on the HRWS SAR system with monostatic architecture.
DLR Import::2019-04-03